Mengembangkan Kreatifitas Anak Usia Dini Melalui Metode Prakarya - Alienra Davry Nanda Kadun (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Creative learning is innovative and inventive that's vital for children. Qahal Ceria Jayapura is a non-profit community that helps to build children's character and creativity. Qahal Ceria faced obstacles in designing creative learning. This community services takes form in assisting teachers to design creative projects and materials. We designed 2 projects, coloring drawings and making ornaments using simple and natural materials. We expect these projects as references and hoped to motivate teachers for further development.